Laughter and Fieldwork in Nagaland: A Dialogue - Kikon, Dolly; Tamma, Krishnapriya (ACME, 2024)
This is a dialogue and reflection about fieldwork, laughter, and decolonizing methodology. Is there a time to laugh? How and why should researchers laugh? By focusing on the Naga people in Northeast India, an Indigenous community with a deep history of militarization, this dialogue draws our attention to the meaning of laughter, fellowship, and emotional connections. An Indigenous Naga anthropologist in conversation with an ecologist, this dialogue dwells on the meaning of laughter as sharing an experience of fellowship together. Social science methodologies are often structured on examinations, investigations interviews, fieldnotes, and observations. This dialogue opens a space to reflect on fieldwork, research, and decolonization. Laughter, as this dialogue highlights, is about affection, solidarity, and collective vision. For any long-term relationship that one seeks to establish as a researcher, acknowledging and respecting the history of the land, adopting a community-approach, and mentoring Indigenous local scholars to lead the research among their respective communities are important steps towards decoloniality.